Turnover and fate of fibrinogen and platelets at the rabbit aorta wall immediately after a balloon de-endothelializing injury in vivo - Hatton, Mark W. C.; Ross, Bonnie; Timleck, Marnie; Southward, Suzanne M. R.; Richardson, Mary (Thrombosis and Haemostasis, 2006)
A de-endothelializing injury to the artery wall in vivo results in a rapid procoagulant response at the surface of the exposed subendothelium. Activated tissue factor (TF)-bearing cells and hemostasis factors located at the site of injury respond by producing thrombin, and within minutes the principal thrombus-forming, blood-borne components (platelets, fibrinogen) accumulate at the site.To compare their behaviors, the rates of uptake and turnover of rabbit 51Cr-platelets and rabbit 125I-fibrinogen were quantified simultaneously during the initial 100-min interval after a balloon catheter injury to the rabbit aorta in vivo.Platelets (∼70,000/mm2) and fibrin(ogen) (∼2.8 pmol/cm2) saturated the ballooned aorta surface within five minutes after injury.Whereas the adherent platelet and fibrinogen concentrations remained steady at the aorta surface, fibrin(ogen)-related products continued to accumulate slowly in the tunica media (TM) for at least 100 minutes. A relatively small proportion (3.7%/min) of adhered platelets turned over at the ballooned aorta surface at 10 minutes, decreasing to 1.2%/min at 100 minutes. By contrast, a larger proportion of fibrin(ogen) (∼ 20%/min) was turned over within the platelet layer at 10 minutes, decreasing to 6%/min at 100 minutes. As verified by immunostaining aorta sections and by protein analysis ofTM extracts,the uptakes of platelets and fibrinogen at the site of injury contributed to an accumulation of products of platelet releasate and fibrin(ogen) degradation (FDPs) within the TM.These observations improve our understanding of the hemostatic processes and subsequent events that occur after an arterial injury in vivo.
Keywords: De-endothelializing injury; rabbit aorta; uptake and turnover of platelets and fibrinogen; platelet releasate; fibrin degradation products